SOCIO-ECONOMIC CONTRADICTIONS THE PROCESS OF GRAIN PRODUCTION CONCENTRATION IN THE BELGOROD REGION - Alina Ivanovna Dobrunova (Science and Innovation Center Publishing House, 2018)
The article discusses the development of grain production in Belgorod region, which is closely related to the concentration of its production, both in agro-industrial formations and in independent agricultural organizations. As a result of the analytical grouping, information on 143 agricultural organizations of Belgorod Region was processed (of which 84 agricultural organizations are independent and 59 are part of the agro-industrial formations). The results of the research show that with an increase in the size of acreage, there is a decrease in the average cost of 1 ton of grain sold, an increase in yield, indicators of the volumes of grain production and profitability. The main problem remains not only the low purchase price for grain, which is indicated by the majority of the heads of agricultural organizations, but also the insufficiently effective management of costs in the production of grain. The increase in the scale of grain production makes it possible to compensate for even a decrease in the selling price, that is, it confirms the existence of significant reserves for increasing efficiency at the expense of production concentration. Agro-industrial formations are engaged in the production of mainly feed grains (about 85%), for domestic use, since they specialize in the production of pig and poultry meat. The concentration of grain production, especially in agribusiness, which owns most of the agricultural land in the region (65%), has a number of negative aspects associated with the inability to ensure sustainable development of rural areas. The formation of agricultural consumer cooperatives or its clustering may become a promising direction for the development of grain production. This will contribute to the growth of economic efficiency of production, the creation of new jobs, the harmonization of the interests of all commodity producers and the development of rural infrastructure.